2017
DOI: 10.1016/j.bone.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

CCL3 and MMP-9 are induced by TL1A during death receptor 3 (TNFRSF25)-dependent osteoclast function and systemic bone loss

Abstract: Reduced bone density and secondary osteoporosis, resulting in increased risk of fracture, is a significant complicating factor in the inflammatory arthritides. While the exact etiology of systemic bone loss is not fully elucidated, recent insights into the tumor necrosis factor super family (TNFSF) revealed a potential role for death receptor 3 (DR3/TNFRSF25) and one of its ligands, TNF-like protein 1A (TL1A/TNFSF15). The mechanisms by which DR3/TL1A signalling modulates bone loss are unclear. We investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 64 publications
2
28
2
Order By: Relevance
“…Flow cytometry confirmed ⩾95% cells were CD14 positive. Purified CD14-positive cells were re-suspended in complete medium (3.2 × 10 6 cells/ml) and seeded onto ivory disks to model cell/substrate interactions on bone matrix [ 26 ]. CD14-positive cells were adhered to the ivory disks, which were subsequently transferred into individual wells containing 500 μl of complete medium containing M-CSF (10 ng/ml).…”
Section: Methodsmentioning
confidence: 99%
“…Flow cytometry confirmed ⩾95% cells were CD14 positive. Purified CD14-positive cells were re-suspended in complete medium (3.2 × 10 6 cells/ml) and seeded onto ivory disks to model cell/substrate interactions on bone matrix [ 26 ]. CD14-positive cells were adhered to the ivory disks, which were subsequently transferred into individual wells containing 500 μl of complete medium containing M-CSF (10 ng/ml).…”
Section: Methodsmentioning
confidence: 99%
“…And the tooth eruption was evaluated by the X ray.Histochemistry, immunohistochemistry, and immunofluorescent stainingFemurs were fixed in 4% paraformaldehyde for 24 h and decalcified in 10% EDTA (room temperature) for 2 weeks. After dehydration in an alcohol gradient (50%, 75%, 85%, 95%, or 100%), femurs were embedded in paraffin, cut into 4 µm thick sections using a Thermo Scientific Microm HM 325 Rotary Microtome, and processed for hematoxylin-eosin (H&E) staining and TRAP staining according the manufacturer's instructions(43). For immunohistochemistry staining, sections were incubated with primary antibodies against RANKL (Abcam; catalog no.…”
mentioning
confidence: 99%
“…Inhibition of Ctsk alleviates bone erosion and cartilage degradation in arthritic mice [26]. In addition, activation of MMP9 and CAII is associated with enhancing osteoclasts formation and resorptive activity [27,28]. Our findings suggested that DOX treatment led to down-regulation of Ctsk, MMP9 and CAII mRNA expression and restored cartilage damage in aging mice, indicating that inhibition of osteoclast activity by DOX might protect against age-related bone injury.…”
Section: Discussionmentioning
confidence: 61%